Marketing Digital: venda de arte gráfica no whatsapp - Forte, Renato Samias (Brasil, 2024)
Digital marketing is a process and activity that uses a platform and channels to promote a brand, product and service over the internet through strategy. This study has the general purpose of: analyzing a marketing strategy on social networks, the sale of graphic art through WhatsApp, on the social network. The investigation had a qualitative nature, the participatory research method, to capture the data, an interview guide was prepared for buyers and sellers. This work is developed with bibliographical research, which is used to develop the research on the topic. This is the result of more current studies of social networks in a virtual environment, due to the large number of individuals being on WhatsApp and the increase in electronic commerce.